Ann-Margret (New York, NY Putnam, 1994)
Ann-Margret has dazzled screen and stage audiences as few entertainers in our time. Her appearance in movies such as Bye Bye Birdie, Carnal Knowledge, and Tommy, and in the acclaimed television miniseries The Two Mrs. Grenvilles and Queen, and her recent record-breaking shows at Radio City Music Hall have made her a woman loved and admired, not just for her beauty and her legend, but for herself. Yet until now the public has known only Ann-Margret the star. Finally, we hear from Ann-Margret the woman. For years the Hollywood gossip mills portrayed her as self-destructive, an actress of bristling nerves, a wife controlled by a Svengali husband, and finally, a tragic heroine. For the first time, Ann-Margret opens the door to her private world, in a memoir that tells her life as it really was. Relentlessly honest, these pages are filled with warmth, wit, poignancy, and truth. Readers will learn of her moving, longtime relationship with Elvis Presley; her battle with and inspiring recovery from alcohol abuse; her loss and reclamation of her self-esteem; and her harrowing twenty-two-foot fall onstage, after which doctors feared she would never dance again. Readers will also learn the story behind her twenty-nine-year love affair with husband Roger Smith, and of his battle with myasthenia gravis, a disease that forced Ann-Margret, who had always been protected by her husband and family, to take control of not only her life but her husband's as well. Here, too, are wonderful behind-the-scenes tales about costars Bette Davis, George Burns, John Wayne, Jack Nicholson, and Steve McQueen, to name a few. But Ann-Margret: My Story is ultimately about this remarkably candid woman herself, finding her own way, seeking independence, becoming an accomplished actress and - more important - a woman of guts, humor, energy, and inspiration
D., 6/02
Keywords: Ann-Margret -- Biography; Entertainers--United States--Biography